#TITLE_ALTERNATIVE# - PRASETYA ARYANI (NIM : 20212007); Pembimbing : Prof. Freddy P.Zen, D.Sc., NILA
In this thesis, analysis of compound KdV-Burgers equation was observed by time series, phase portrait and Poincare map method. Disruption given to the compound KdV-Burgers equation was in the form of periodic disturbances. This equation can applied in the aneurysm of blood vessels. The investigation were done with variation of g and w which is represent pulse pressure and cardiac frequency of heart. Result of MATLAB simulation shown that chaotic behaviour can occur in the compound KdV-Burgers equation with periodic perturbation. Chaotic behaviour which happened caused by variation of g and w. Beside that, there was a minimum and maximum value of g and w which made the chaotic behaviour of the system. Chaotic behaviour indicate that blood flow in the aneurysm was turbulence. Different value of g and w can cause different behaviour of the system. Higher of value of g and w, risk of rupture aneurysm can increase. This will increase the risk of death.